2016
DOI: 10.4137/jen.s39887
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Oxygen Species: Physiological and Physiopathological Effects on Synaptic Plasticity

Abstract: In the mammalian central nervous system, reactive oxygen species (ROS) generation is counterbalanced by antioxidant defenses. When large amounts of ROS accumulate, antioxidant mechanisms become overwhelmed and oxidative cellular stress may occur. Therefore, ROS are typically characterized as toxic molecules, oxidizing membrane lipids, changing the conformation of proteins, damaging nucleic acids, and causing deficits in synaptic plasticity. High ROS concentrations are associated with a decline in cognitive fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
174
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(181 citation statements)
references
References 370 publications
(605 reference statements)
2
174
0
5
Order By: Relevance
“…Without going into the details of ROS-mediated signaling cascades, our results indicate that exogenous and endogenous ROS may play similar roles in synaptic plasticity mechanism. In addition, other studies have shown that exogenous ROS species induce similar patterns of protein activation (e.g., protein kinase C, Ca 2+ /calmodulin-dependent protein kinase II, AMPA, cAMP response element-binding protein, extracellular signal-regulated kinases) to that induced by nerve injury- or conditioning stimulus-increased ROS 2,8 . Furthermore, our previous study showed that CS- and tBOOH-induced synaptic plasticity cancel each other supporting that endogenous and exogenous ROS might share a signaling cascade or converge at a certain step along the pathway when it comes to synaptic plasticity 22 .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Without going into the details of ROS-mediated signaling cascades, our results indicate that exogenous and endogenous ROS may play similar roles in synaptic plasticity mechanism. In addition, other studies have shown that exogenous ROS species induce similar patterns of protein activation (e.g., protein kinase C, Ca 2+ /calmodulin-dependent protein kinase II, AMPA, cAMP response element-binding protein, extracellular signal-regulated kinases) to that induced by nerve injury- or conditioning stimulus-increased ROS 2,8 . Furthermore, our previous study showed that CS- and tBOOH-induced synaptic plasticity cancel each other supporting that endogenous and exogenous ROS might share a signaling cascade or converge at a certain step along the pathway when it comes to synaptic plasticity 22 .…”
Section: Discussionmentioning
confidence: 97%
“…On the other hand, TEMPOL and DMTU are commonly used, well characterized, cell permeable endogenous ROS scavengers. However, it is not clear whether endogenous and exogenous ROS exposure influence the cellular proteins and signaling cascades similarly or differently 2 . In our study, we investigated the effect of both ROS donors and scavengers on STTn and GABAn synaptic excitability.…”
Section: Discussionmentioning
confidence: 99%
“…ROS, while often thought of as harmful molecules involved in cell damage and death, are also important signaling molecules when properly regulated and controlled (Kamsler and Segal, ; Kishida and Klann, ; Beckhauser et al, ).…”
Section: Microglia Modification Of Neuronal Activitymentioning
confidence: 99%
“…ROS initiate lesion formation by inducing the BBB disruption, enhance leukocyte migration and myelin phagocytosis. ROS by inducing cellular damage to essential biological structures of vulnerable CNS cells contribute to lesions persistence (Beckhauser et al 2016). The presence of extensive damage to lipids, proteins and nucleotides occurring in the active demyelinating MS lesions, predominantly in reactive astrocytes and myelin laden macrophages was presented by van Horssen and colleagues (2008).…”
Section: Reactive Oxygen Species and Reactive Nitrogen Species In Mulmentioning
confidence: 99%